Cambodia’s Inclusive Education Development from 1953 to 2024: A Literature Review - Wen Rouet; Rany Sam; Virak Keo; Bunrosy Lan; Chandarey Vong (MultiTech Publisher, 2024)
Cambodia, like many other nations globally, has instituted policies for inclusive education and crafted an educational strategic plan to foster advanced knowledge and professional ethics among individuals with disabilities. The evolution of Cambodia's inclusive and special educational institutions has been influenced by colonization, political ideologies, and global economic trends. This paper thoroughly examines the trajectory of inclusive education across six phases of political change, assessing the achievements and shortcomings of each regime in implementing inclusive education as a driver for national development. Drawing on a comprehensive review of scholarly articles, the research is a valuable resource for scholars, educators, and policymakers aiming to enhance their understanding of Cambodia's history in special and inclusive education. It emphasizes the need for reforms to ensure equal educational opportunities and academic success for students with disabilities.